American visions of the Netherlands East Indies/Indonesia : US foreign policy and Indonesian nationalism, 1920-1949 - Gouda, Frances, 1950- (Amsterdam University Press, 2002)
A revealing reassessment of the American government's position towards Indonesia's struggle for independence.